Efektivitas Senam Hamil Dalam Mengurangi Tingkat Stres dan Kecemasan Ibu Hamil Trimester III: Literature Review - Suwito, Suyati; Alpiah, Dini Nur (Jurnal Fisioterapi Terapan Indonesia, 2025)
According to WHO (2020), around 10% of pregnant women experience depression and this condition is higher in developing countries, reaching 15.6% during pregnancy and 19.8% after giving birth. Anxiety experienced during pregnancy can have negative effects on both the mother and the fetus. These negative impacts are not only during pregnancy but can also affect the labor process and lactation period. There are various types of sports to reduce anxiety, one of which is gymnastics. This study aims to determine the effectiveness of pregnancy gymnastics in reducing stress and anxiety before childbirth. Literature review research was conducted using PICO search in databases such as Google Scholar and Pubmed. 5 journals were obtained that met the criteria and stated that the effect of gymnastics or physical activity had an effect on the level of anxiety reduction in primigravida pregnant women in the third trimester in facing the labor process. It can be concluded that pregnancy gymnastics can reduce stress and anxiety levels in pregnant women before childbirth.